Between Reality and Fantasy: Home in Ransom Riggs's Miss Peregrine's Home for Peculiar Children. Issue 1 (2nd January 2022) - Chang, Hawk
ABSTRACT: In the postmodern era, the notion of home has significant changes. An increasing number of eccentric characters, which used to be invisible in or excluded from classical discourse, have now increasingly come to the fore. Due to their eccentricities, these characters do not seem to belong in places that fit the traditional conception of home, and so they often inhabit imaginary places. Harry Potter calls Hogwarts home, the mutants of X-Men reside in the Professor's school, and the children in Miss Peregrine's Home for Peculiar Children seek shelter in the orphanage run by Miss Peregrine. Through a reading of Ransom Riggs's 2011 book Miss Peregrine's Home for Peculiar Children, I argue that people's craving for a secure home, along with the awareness of their ultimate homelessness, is a dilemma that has always troubled humans and continues to trouble them even in the twenty-first century.